Limiting antenatal weight gain improves maternal health outcomes in severely obese pregnant women: findings of a pragmatic evaluation of a midwife-led intervention - McGiveron, Ailsa; Foster, Sally; Pearce, Joanne; Taylor, Moira A.; McMullen, Sarah; Langley-Evans, Simon C. (Wiley, 2014)
Background: Antenatal obesity in pregnancy is associated with complications of pregnancy and poor obstetric outcomes. Although most guidance on pregnancy weight is focused on the pre-pregnancy period, pregnancy is widely viewed as a period where women are open to lifestyle change to optimise their health.